PENGGUNAAN DERET IN UNTUK MENENTUKAN RERATA ORDE TINGGI FUNGSI POLINOMIAL DENGAN CARA LANGSUNG - Stephanus Ivan Goenawan; Kumala Indriati (UNEJ e-Proceeding, 2022)
The High Order Average (ROT) value in the data is an extension of the First Order Mean. There are two methods to find the High Order Average, namely the first step by step and the second directly. The ROT method can directly use the IN Series. Because the process of adding data in stages does not need to be done one by one, the direct ROT method is more effective and efficient. In this study, the two methods will be compared to each other with the results of calculating the ROT data from polynomial functions. ROT calculation results from both methods have the same value. Keywords: Average, IN Series, Interpolation, ROT